2022
DOI: 10.1002/1878-0261.13343
|View full text |Cite
|
Sign up to set email alerts
|

SMG1, a nonsense‐mediated mRNA decay (NMD) regulator, as a candidate therapeutic target in multiple myeloma

Abstract: Early data suggested that CC-115, a clinical molecule, already known to inhibit the mammalian target of rapamycin kinase (TORK) and DNAdependent protein kinase (DNA-PK) may have additional targets beyond TORK and DNA-PK. Therefore, we aimed to identify such target(s) and investigate a potential therapeutic applicability. Functional profiling of 141 cancer cell lines revealed inhibition of kinase suppressor of morphogenesis in genitalia 1 (SMG1), a key regulator of the RNA degradation mechanism nonsense-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Along with having a crucial role in identifying the SMG1–UPF2–SMG7 complex within the NMD process, the SMG1 genes have been shown distinguishable in tasks in the alternative splicing of the tumour-suppressor p53 genes [ 25 ]. Due to the different activities of SMG1 in multiple myeloma (MM) cell lines [ 26 ], it has become a promising therapeutic target for the development of novel drug molecules. The activation of the SMG1-UPF within the NMD pathway has shown a downregulation of negative regulator MDM2 (Murine Double Minute Clone 2) by Glaucocalyxin A in Gastric cancer (GC) cells [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Along with having a crucial role in identifying the SMG1–UPF2–SMG7 complex within the NMD process, the SMG1 genes have been shown distinguishable in tasks in the alternative splicing of the tumour-suppressor p53 genes [ 25 ]. Due to the different activities of SMG1 in multiple myeloma (MM) cell lines [ 26 ], it has become a promising therapeutic target for the development of novel drug molecules. The activation of the SMG1-UPF within the NMD pathway has shown a downregulation of negative regulator MDM2 (Murine Double Minute Clone 2) by Glaucocalyxin A in Gastric cancer (GC) cells [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study found potential targets by targeting the key NMD factor UPF1 to bind the fragile X syndrome protein FMRP (Kurosaki et al, 2021). The NMD regulator SMG1 has been shown to be a candidate therapeutic target for multiple myeloma (Leeksma et al, 2023). Moreover, relevant studies have shown that the NMD factor UPF2 is a key target for the treatment of early embryonic lethality (Chousal et al, 2022).…”
Section: B Practical Application Of Disease-centred Target Discovery ...mentioning
confidence: 99%
“…The latter can detect and destroy aberrant transcripts with premature termination codons (PTCs), preventing potentially harmful proteins from being translated [10]. During the process, a number of frameshift mutations may avert from NMD, and probably induce immune reactions [11]. Many previous studies also have indicated that abnormal transcripts which evade from NMD may encode neoantigens potentially triggering immune responses in cancer patients [12][13][14].…”
Section: Introductionmentioning
confidence: 99%